Expression of EMMPRIN as a biomarker in nonodontogenic carcinomas: a histological study - Antisar, Ben Amer M.; Enas, Omar M.; Sahar, Elsheikh M.; Ahmed, Musrati S. (Taylor & Francis, 2026)
EMMPRIN is a widely distributed cell surface glycoprotein that belongs to the immunoglobulin (Ig) superfamily. It induces the production of extracellular matrix metalloproteinases (MMPs) and plays an important role in angiogenesis via stimulation of vascular endothelial growth factor (VEGF). The aim of the present work was to assess and compare the expression of extracellular matrix metalloproteinase inducer (EMMPRIN) in different oral nonodontogenic carcinomas. Fifty-four diagnosed cases of oral nonodontogenic carcinomas were selected, and biopsies were taken from the tumor tissue, fixed, processed, and cut into sections to be stained with hematoxylin and eosin (H&E) for routine histopathological examination. Immunohistochemistry was performed for EMMPRIN. All cases showed positive EMMPRIN expression with different intensities. The results were recorded and statistically analyzed using student t-test, Pearson correlation, test and ANOVA test. This study concluded that elevated EMMPRIN expression is correlated with tumor proliferation, angiogenesis, metastasis, and invasion.